Asian-American Identity and Cultural Displacement in Everything Everywhere All at Once (2022) - Bayu Firmansyah Rianto; Krisna Sujiwa (Sasdaya: Gadjah Mada Journal of Humanities, 2026)
This study analyzes Everything Everywhere All at Once from a postcolonial perspective, focusing on the formation of Asian-American identity through themes of diaspora, cultural displacement, and intergenerational conflict. Drawing on Homi K. Bhabha’s concepts of hybridity and the “third space,” the research demonstrates how the film portrays identity as a dynamic and ongoing process within a Western-dominated cultural framework. The characters of Evelyn and Joy serve as central figures in illustrating the tension between cultural heritage and assimilation, as well as the emotional complexities of navigating family expectations and personal autonomy. Using qualitative textual and visual analysis, this study examines narrative structure, dialogue, and cinematic elements to reveal how the film represents immigrant experiences in a nuanced and multidimensional way. Furthermore, the multiverse is interpreted as a symbolic representation of fragmented and fluid identities, where multiple realities reflect the instability and plurality of diasporic existence. The generational divide between Evelyn and Joy further intensifies these conflicts, highlighting differences in values, identity expression, and cultural adaptation within immigrant families. In addition, the film emphasizes how cultural hybridity functions not only as a site of conflict but also as a creative space for negotiating belonging and selfhood. Ultimately, the study concludes that the film successfully captures the complexities of diasporic subjectivity, emphasizing that identity is not fixed but continuously negotiated within intersecting cultural spaces.